1990
DOI: 10.1088/0953-8984/2/19/014
|View full text |Cite
|
Sign up to set email alerts
|

Neutron powder diffraction study of the two-dimensional triangular lattice antiferromagnet CuCrO2

Abstract: An S = 9 Heisenberg antiferromagnet on a triangular lattice CuCr02, in which stacking of the triangular lattice of magnetic Cr atoms forms a layered rhombohedral antiferromagnet, is studied by neutron powder diffraction. In the paramagnetic phase the powder diffraction pattern shows asymmetry, which proves a two-dimensional character. In the ordered phase, magnetic Bragg scattering has large width, indicating that the scattering is distributed on a line ($4 b) with peaks where 5 takes integer values. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
85
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 21 publications
13
85
3
Order By: Relevance
“…The correlation length is therefore larger than at least several hundredÅ. This result clearly disagrees with the conclusions from the powder diffraction measurements [10,11] (which were suggesting short range order along the L-direction).…”
Section: Resultscontrasting
confidence: 89%
See 2 more Smart Citations
“…The correlation length is therefore larger than at least several hundredÅ. This result clearly disagrees with the conclusions from the powder diffraction measurements [10,11] (which were suggesting short range order along the L-direction).…”
Section: Resultscontrasting
confidence: 89%
“…The latter is in better agreement with the occurrence of 3-dimensional order, although it had been shown that an interlayer exchange has to be relatively small (<0.2meV) [24]. The maximum ordered moment in our model is 2.8(2) µ B which is close to the expected 3 µ B for the Cr 3+ ion and the reported values from the powder measurements [10,11]. An additional uncertainty for the absolute moment value from the single crystal measurements comes from the non-equal domain distribution.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Lattice parameters and anisotropic atomic displacement parameters were refined at all temperatures. The lattice parameters exhibit temperature behaviors consistent with literature values, with the c-axis displaying a negative thermal expansion, and the a-axis displaying normal thermal expansion [10,41].…”
Section: Inelastic X-ray Scatteringsupporting
confidence: 83%
“…The introduction of charge carriers, which is possible in some delafossite compounds, may further induce novel phenomena arising from the coupling between the magnetic and transport properties in the quasi-two-dimensional frustrated triangular lattice. The magnetic degeneracy was lifted and the no collinear magnetic structure was realized in the antiferromagnetic (AF) regime below the ordering temperature (T N ) to resolve the magnetic frustration [18,19]. This magnetic frustration appeared to be removed by the introduction of some trivalent cations in M-sites.…”
Section: Introductionmentioning
confidence: 99%